The Impact of Inclusive Sports Learning on Improving Motor Skills of Students with Special Needs - Muhammad Nurul Akbar Adityatama; Naela Mikyalul Faizah (Journal of Salutare, 2024)
This study aims to analyze the impact of inclusive sports learning on improving motor skills of students with special needs, using a literature study method. A review of various relevant literature sources shows that inclusive sports learning has significant potential in improving motor skills, such as coordination, balance, muscle strength, and reflex skills. Structured and adaptively designed physical activities allow students with special needs to participate actively, contributing to better physical development. An inclusive learning environment, where students feel accepted and supported, plays a major role in increasing self-confidence and motivation to engage in physical activity. Social interactions that occur during sports activities also help students strengthen social skills, such as cooperation, communication, and empathy. The findings of this study emphasize the importance of implementing the principle of inclusion in physical education and the need to develop a curriculum that is responsive to the needs of diverse students. Recommendations for educators and policy makers include integrating inclusive sports practices into the education system, training for educators to address diversity in the classroom, and providing adequate resources to support learning. This research is expected to contribute to improving the quality of learning for all students, especially those with special needs, thereby creating a more just and equitable educational environment.